Microbial Community Changes in 26,500-Year-Old Thawing Permafrost - Scheel, Maria; Zervas, Athanasios; Jacobsen, Carsten S.; Christensen, Torben R. (Frontiers in Microbiology, 2022)
Northern permafrost soils store more than half of the global soil carbon. Frozen for at least two consecutive years, but often for millennia, permafrost temperatures have increased drastically in the last decades. The resulting thermal erosion leads not only to gradual thaw, resulting in an increase of seasonally thawing soil thickness, but also to abrupt thaw events, such as sudden collapses of the soil surface. These could affect 20% of the permafrost zone and half of its organic carbon, increasing accessibility for deeper rooting vegetation and microbial decomposition into greenhouse gases. Knowledge gaps include the impact of permafrost thaw on the soil microfauna as well as key taxa to change the microbial mineralization of ancient permafrost carbon stocks during erosion. Here, we present the first sequencing study of an abrupt permafrost erosion microbiome in Northeast Greenland, where a thermal erosion gully collapsed in the summer of 2018, leading to the thawing of 26,500-year-old permafrost material. We investigated which soil parameters (pH, soil carbon content, age and moisture, organic and mineral horizons and permafrost layers) most significantly drove changes of taxonomic diversity and the abundance of soil microorganisms in two consecutive years of intense erosion. Sequencing of the prokaryotic 16S rRNA and fungal ITS2 gene regions at finely-scaled depth increments revealed decreasing alpha diversity with depth, soil age and pH. The most significant drivers of variation were found in the soil age, horizons and permafrost layer for prokaryotic and fungal beta diversity. Permafrost was mainly dominated by Proteobacteria and Firmicutes, with Polaromonas was identified as the most abundant taxon. Thawed permafrost samples indicated increased abundance of several copiotrophic phyla, such as Bacteroidia, suggesting alterations of carbon utilization pathways within eroding permafrost.